2022
DOI: 10.1212/wnl.0000000000200836
|View full text |Cite
|
Sign up to set email alerts
|

Pearls & Oy-sters: Challenges and Controversies in Wilson Disease

Abstract: WD is a genetic disorder of copper metabolism caused by mutations in the ATP7B gene, which are inherited in an autosomal recessive pattern. Despite all the advances made on pathogenesis, cellular biology and genetics, to date WD remains a diagnostic and therapeutic challenge. With this series of cases, we aim to illustrate the main challenges that clinicians may encounter when dealing with WD patients: the difficulties with clinical diagnosis, the therapeutic management of WD and the indication for advanced th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
0
0
0
Order By: Relevance
“…ECG abnormalities were found in 19 patients, including premature ventricular contractions (n = 4), sinus bradycardia (n = 11), and sinus arrhythmia (n = 4). The median UWDRS score of WD-neuro + patients was 6.0 (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11).…”
Section: Baseline Characteristicsmentioning
confidence: 97%
See 1 more Smart Citation
“…ECG abnormalities were found in 19 patients, including premature ventricular contractions (n = 4), sinus bradycardia (n = 11), and sinus arrhythmia (n = 4). The median UWDRS score of WD-neuro + patients was 6.0 (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11).…”
Section: Baseline Characteristicsmentioning
confidence: 97%
“…Copper overload mainly occurs in the liver and brain and causes a variety of liver damage and neurological symptoms. Patients can be divided into WD-neuro + (patients with at least one neurological symptom) and WDneuro − (patients with a primarily hepatic involvement) patients [5,6]. However, several studies have shown that copper deposition can also occur in the heart and lead to clinical symptoms of related cardiovascular disease (e.g.…”
Section: Introductionmentioning
confidence: 99%